Role of Local Tourism Governance Policies in Achieving Sustainable Tourism Development: A PLS-SEM Modeling Study - Rahaju, Tjitjik; Megawati, Suci; Prabawati, Indah; Suprapto, Firre An; Muzaqi, Ajie Hanif; Ardiyansyah, Ardiyansyah (International Review of Management and Marketing, 2026)
Tourism development has increasingly become central to sustainable economic strategies, particularly in culturally and environmentally rich nations such as Indonesia. Despite the sector’s contribution to GDP and employment, challenges in balancing environmental preservation, cultural integrity, and infrastructure development persist. This study aims to investigate the role of local tourism governance policies—specifically nature, cultural activity, recreation, and infrastructure development policies—in fostering sustainable tourism. Utilizing a quantitative approach, data were collected from 200 local government staff responsible for tourism in Indonesia. Partial Least Squares Structural Equation Modeling (PLS-SEM) was employed to assess the structural relationships between policy types, community participation, and sustainable tourism development. The findings confirm significant positive effects of all four policy domains on sustainable tourism. Moreover, community participation significantly moderates the effectiveness of cultural and recreational policies but not nature or infrastructure policies. The study contributes theoretically by integrating governance frameworks with sustainability discourse, emphasizing the differentiated roles of policy types and community involvement. Practically, the findings highlight the need for policymakers to integrate inclusive participation mechanisms—especially in technical policy areas—to ensure comprehensive tourism sustainability. The results provide actionable insights for designing context-sensitive, community-empowered tourism strategies in developing nations.